PENINGKATAN PENGETAHUAN KADER POSYANDU TENTANG STUNTING DI WILAYAH KERJA PUSKESMAS SIMPANG KAWAT KOTA JAMBI - Gustina, Gustina (Jurnal Abdimas ADPI Sains dan Teknologi, 2020)
The important role of Posyandu cadres as the front guard in providing services to thecommunity through Posyandu. Posyandu cadres are people who are chosen, willing, capable, andhave the time and care for basic social services for the community. Therefore, training for Posyanducadres is an effort to increase the capacity and capability of Posyandu cadres.Activities at the Posyandu are aimed, among others, to monitor the weight growth of childrenunder five using the Card Towards Healthy (KMS), provide nutritional counseling, and providebasic nutrition and health services, which are closely related to stunting. The intervention effortsmade by the Ministry of Health, point 4, to monitor the growth of children under five at posyanduare very strategic efforts to detect early growth disorders.Stunting is a problem because it is associated with an increased risk of illness and death,suboptimal brain development so that motor development is delayed and mental growth is inhibited.Several studies have shown the risk caused by stunting, namely decreased academic achievement,increased risk of obesity, more susceptibility to non-communicable diseases and an increased risk ofdegenerative diseases.This community service is to provide education in an effort to increase posyandu cadres'knowledge about stunting. The method used is the pretest and posttest evaluation. The results andconclusions were that there was an increase in the knowledge of posyandu cadres after healtheducation was carried out on stunting.